GLOMERULAR PERMEABILITY : ULTRASTRUCTURAL CYTOCHEMICAL STUDIES USING PEROXIDASES AS PROTEIN TRACERS - Graham, Richard C. (The Rockefeller University Press, 1966)
1. Glomerular permeability was studied by ultrastructural cytochemistry, using as protein tracers two intravenously injected peroxidases of differing molecular weight. 2. Horseradish peroxidase (molecular weight 40,000) passed rapidly through the endothelial fenestrae, across the basement membrane, and through the epithelial slits into the urinary space. Human myeloperoxidase (molecular weight 160,000 to 180,000) also passed rapidly through the endothelial fenestrae and across the basement membrane, but was impeded at the level of the epithelial slits. Both proteins were taken up in large amounts by the mesangial cells. 3. The present findings indicate that the epithelial slits are the primary filtration barrier responsible for the differential permeability to proteins of varying molecular size. 4. The observations also support the concept that an important function of the mesangial cells is the incorporation and disposal of glomerular filtration residues.